Influence of Actuator Nozzle Angle on the Flow Characteristics in Pressurized-Metered Dose Inhaler Using CFD - Abd Rahman, Muhammad Faqhrurrazi; Asmuin, Nor Zelawati; Taib, Ishkrizat; Hidayat Mat, Mohamad Nur; Khairulfuaad, Riyadhthusollehan (Penerbit Akademia Baru, 2020)
Pressurized metered dose inhalers (pMDIs) are often used for the treatment of asthma and chronic obstructive pulmonary disease. This device is easy to carry, highly effective and extremely safe, allowing reliable, consistent dosage delivery, metered dose inhalers are the inhalation devices that doctors and patients can readily select from around the world. This pMDI inhaler system has a problem which is the particle does not penetrate into the alveolar. ANSYS Fluent Version 19.2 was used to find the best angle of the actuator nozzle by parametric analysis. Standard K-epsilon was used as the turbulence model with enhanced wall treatment function. Discrete phase model (DPM) was applied to represent the particle flow. The result shows the best actuator nozzle angle is 120-degree which affects the maximum magnitude of particle velocity.